INVESTMENTS IN HUMAN CAPITAL DEVELOPMENT - BOIKIVSKA, Galyna; OVCHARUK, Olekcandr; KHANYK, Andrii (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article elucidates the significance of human capital for enterprises and society as a whole. It underscores the importance of investing in human capital as a strategic component of economic development. Investment in education, professional development, and health not only contributes to the growth in worker efficiency but also lays the foundation for sustainable economic growth and social upliftment. Such an approach not only ensures economic benefits for individuals and society but also enhances quality of life and ensures future stability. Implementing a systemic approach to human resource management opens opportunities for adaptation to changes in the socio-economic environment and enhances competitiveness, crucial factors for societal stability. Particularly, it is noted that companies prioritizing their workforce development become more competitive and hold leading positions in their sectors. The significance of investing in human capital to achieve sustainable competitive advantage is highlighted as a key element of strategic management. Furthermore, the functioning of human capital in the contemporary socio-economic system is examined. Effective human capital management entails integrated approaches to enhancing competitiveness and personal development of the workforce. It is also highlighted that the classification of human capital elements is pivotal for modern enterprises, encompassing strategy formulation, performance monitoring, development plan adjustments, and investor communication. This understanding helps enterprises ensure sustainable development and success in the market. Investments in human capital must become a key factor in addressing challenges related to potential labor shortages resulting from the return of Ukrainians from abroad. The human capital development policy should focus on preserving and developing a capable workforce and youth in Ukraine, as well as facilitating the return of Ukrainians and attracting foreign labor. Investment in education, skill enhancement, labor market support, and other measures will facilitate conditions for effective utilization of workforce potential, mitigate the risk of labor shortages, and ensure economic development stability.
Keywords: management; human development; human capital; investments; professional development